Edukasi Urgensi Menjaga Kesehatan pada Masa New Normal kepada Masyarakat di Sekitar SDN 02 Cipaisan - Muhammad Rifki Mauludin; Evelyn Sinaga; Rifqi Arman Hidayah; Rina Clarita; Septiana Bagus Prayuga; Sri Margi Utami Febiani; Yuyu Hendawati; Fitri Nuraeni (Jurnal Pengabdian Masyarakat PGSD, 2021)
Covid-19 (Corona Virus Disease-19) Pandemic firstly discovered in December 2019 in Wuhan City. All sectors are expected to comply with established protocols to limit physical distancing and avoid crowds.  With all efforts made by the community and the government, the spread of Covid-19 will not end until 2021. The government introduced the term New Normal which means people must live adapting to this virus, carrying out all the usual activities by complying with health protocols, such as: using hand sanitizer, washing hands, paying attention to capacity in one room, checking the temperature, and wearing mask. In Purwakarta, some schools have conducted offline learning, this can be one of the causes of the spread of the Covid-19 virus, so there needs to be education related to the importance of maintaining health in this New Normal. From this problem, the researchers presented the program entitled seminar on the urgency of maintaining health in the new normal in the community of SDN 02 Cipaisan. The implementation of this service is carried out online and offline. Presenters provide material online while participants follow offline while adhering to applicable health protocols. From the data collection through questionnaires taken before and after the seminar, it was obtained that teachers and parents are increasingly aware and aware of the importance of maintaining health during the Covid-19 pandemic.